The Bible in the liturgy of personal ordinariates for former Anglicans – selected theological problems - Beyga, Paweł (The Bible as a meeting place for Christian denominations, 2022)
In 2009 Pope Benedict XVI promulgated apostolic constitution Anglicanotum coetibus. In thisspecial document pope opened the way for conversion of conservative members of the Church ofEngland. Former Anglicans exist in the Catholic Church in three personal ordinariates and usespecial liturgical book for the Holy Eucharist. The main goal of the text is to show biblical elementin the liturgy of the holy mass celebrated according to Divine Worship: The Missal. The authorlooked at the Anglican theology, ordo of the mass in personal ordinariates and theology of JohnHenry Newman – the most famous former Anglican in the history of Catholicism.